Colors 1800/1900/2000: signs of ethnic difference - Tautz, Birgit (Rodopi, 2004)
Preliminary Material /Birgit Tautz – Introduction: Colors and Ethnic Difference or Ways of Seeing /Birgit Tautz – Die Erfindung der ‘Rasse’ um 1800 – Klima, Säfte und Phlogiston in der Rassentheorie Immanuel Kants /Gudrun Hentges – Black Skin, White Skin and the Aesthetics of the Female Body in: Karl Friedrich Wilhelm Ziegler’s Die Mohrinn /Wendy Sutherland – The Whiteness of Beauty: Weimar Neo-Classicism and the Sculptural Transcendence of Color /Daniel Purdy – The Eye of the Ethnographer: Adalbert von Chamisso's Voyage Around the World /Assenka Oksiloff – Seeing Eyes, Reading Bodies: Visuality, Race and Color Perception or a Threshold in the History of Human Sciences /Thomas R. Miller – “Our European Arrogance”: Wilhelm Worringer and Carl Einstein on Non-European Art /Andreas Michel – Mohrenwäschen, Völkerschauen: Der Konsum des Schwarzen um 1900 /Nana Badenberg – Ẃe are Germans, We are Whites, and We Want to Stay White!Áfrican Germans and Citizenship in the early 20th Century /Fatima El-Tayeb – Shame on the Skin: Post-Holocaust Memory and the German Aesthetics of Whiteness /Uli Linke – Colouring the invisible: The figure of the ‘black drug dealer’ as a projection of socially produced fears /Christine Achinger – Orfeo and Sam: Racial, Sexual, and Ethnic Otherness in Dörrie’s Keiner liebt mich (1994) and Sanoussi-Bliss’ Zurück auf los (1999) /Helen Cafferty – Epilog: Farblose Räume /Birgit Tautz. By recasting instances of ‘German’ cultural production around the turns of centuries – 1800, 1900, 2000 – the essays in this volume examine the role that color has played in perceiving and representing ethnic difference. In innovative essays, literary scholars, historians, anthropologists and art historians support an overarching thesis: that the ‘origins’ of a modern, ‘ethnic’ imagination, inscribe patterns of seeing, whereas more recent developments involve processes of de-colorization and metaphorization. By preserving the difference in disciplinary approaches, methods and writing styles, the volume presents a genuinely interdisciplinary approach to German Studies, and is therefore of interest to Germanists, as well as to all others engaged in the study and scholarship of German Culture. Contributors: Christine Achinger, Nana Badenberg, Helen Cafferty, Fatima El-Tayeb, Gudrun Hentges, Uli Linke, Andreas Michel, Thomas Miller, Daniel Purdy, Assenka Oksiloff, Wendy Sutherland, Birgit Tautz. Der Band untersucht die Rolle der Farbe in Prozessen der Wahrnehmung und Darstellung ethnischer Unterschiede in der deutschsprachigen Kultur an drei Jahrhundertwenden: 1800, 1900, 2000. Die interdisziplinären Essays von Literaturwissenschaftlern, Historikern, Anthropologen und Kunsthistorikern bieten Lesarten, die sich auf vielfältige Phänomene beziehen und die These unterstützen, daß das Ethnische zunächst überwiegend visuell vorgestellt und versprachlicht wurde, bevor es einer zunehmenden Metaphorisierung und “Entfärbung” unterlag. Die angebotenen Deutungsmuster repräsentieren keine kohärente Wahrheit; vielmehr sind sie als Symptome unterschiedlicher Wissensformationen, d.h. unterschiedlicher Disziplinen, Methoden und “Schreibverfahren“, zu sehen. Mit Beiträgen von Achinger, Badenberg, Cafferty, El-Tayeb, Hentges, Linke, Michel, Miller, Purdy, Oksiloff, Sutherland, Tautz
10.1163/9789004334427
Keywords: Aufsatzsammlung; German literature; Ethnicity in literature; Germans; Whites; Self (Philosophy); Other (Philosophy); Germans; Ethnic identity; Whites; Race identity; Criticism; interpretation; etc